2002
DOI: 10.1046/j.1365-2141.2002.03373.x
|View full text |Cite
|
Sign up to set email alerts
|

CD34+/CD90+ cells infused best predict late haematopoietic reconstitution following autologous peripheral blood stem cell transplantation

Abstract: Summary.  This study aimed to identify which graft product subset of cells might be the most predictive of late haematopoietic recovery (three to 12 months) following autologous peripheral blood stem cell transplantation (PBSCT). The relationships between the numbers of reinfused CD34+ cells and their immature subsets such as CD34+/CD90+, CD34+/AC133+, CD34+/CD38– and CD34+/HLA‐DR– cells, and haemoglobin, white blood cell (WBC) and platelet counts at 3, 6, 9 and 12 months after PBSCT, were studied in 25 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
1
25
0
3
Order By: Relevance
“…These Ccsp + cells were found in the plastic-adherent fraction and expressed some markers used to characterize mesenchymal cells (22). However, CD90 and CD105 are also known to be expressed in CD45 + hematopoietic precursors (23,24). Several reports have suggested that there is a developmental relationship between hematopoietic stem cells and their mesenchymal progenitors, in which nonadherent hematopoietic cells that can reconstitute the blood have also been shown to give rise to stromal cells (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…These Ccsp + cells were found in the plastic-adherent fraction and expressed some markers used to characterize mesenchymal cells (22). However, CD90 and CD105 are also known to be expressed in CD45 + hematopoietic precursors (23,24). Several reports have suggested that there is a developmental relationship between hematopoietic stem cells and their mesenchymal progenitors, in which nonadherent hematopoietic cells that can reconstitute the blood have also been shown to give rise to stromal cells (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…CD90 is of particular interest, because its expression is associated with a subset of CD34 + stem cells that are predictive of successful hematopoietic engraftments evaluated in cancer patients undergoing peripheral blood stem cell transplantations (35). The expression of CD90 on EPC and pericytes may be indicative of Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Three of five subsequent studies analyzing the threshold value for CD34 þ CD90 þ linÀ cells shared these results. 22,26 However, as seen in Table 2 neither the threshold nor the phenotype of cells to predict platelet engraftment was found to be consistent among these trials. Of note, this population must not be confused with MSCs, which are CD34ÀCD90 þ LinÀ.…”
Section: Introductionmentioning
confidence: 96%
“…CD34 þ /90 þ cells were better predictors of engraftment than the other subpopulations analyzed. 26 The number of CD34 þ / CD90 þ cells constitute approximately one-fourth of the total CD34 þ cells and are generally fewer than the CD34 þ /CD133 þ cells, but more highly represented than the CD34 þ /CD38 --cells. CD34 þ /CD90 þ cells are mobilized into blood at a maximum level a few days earlier than peak mobilization of the total CD34 þ cells.…”
Section: Introductionmentioning
confidence: 99%